Management of land reclamation quality for agricultural use in opencast mining - Terekhov, Yevgen; Litvinov, Yurii; Fenenko, Volodymyr; Drebenstedt, Carsten (Dnipro University of Technology, 2021)
Purpose. Theoretical substantiation of principles and development of recommendations for the choice of technological variant to form the quality of lands of technogenic origin, which would ensure rational spending of funds allotted for reclamation and preservation of the reclaimed lands suitability for agricultural use with the highest requirements for agrophysical soil characteristics. Methods. The following methods were used in the process of the research: the method of theoretical generalization and systematization (to determine the characteristics peculiar to the formation of qualitative characteristics of man-made soil using mechanization of reclamation works), analytical (to determine the factors influencing the effectiveness of land reclamation in opencast mining), comparison (to analyze the efficiency of different versions of reclamation works mechanization). Findings. The influence of technical means of reclamation works mechanization on the quality of lands subject to restoration in conditions of opencast mining is analyzed. A methodological approach to the choice of mechanization of land reclamation works in respect to the indicators of the formed quality of technogenic agricultural lands as a factor of their monetary valuation and the level of costs for their reproduction is proposed. Recommendations for quality management of man-made lands by technical support of the process of their consumer properties formation, aimed at achieving a favorable ratio between quality and, accordingly, monetary valuation of man-made lands, on the one hand, and, on the other, – the cost of their reclamation. Originality. A scientific and methodological approach to the choice of technical equipment for reclamation works is proposed, where two factors are considered: reclamation costs and quality of man-made lands, which allows to determine the priority of cost savings or land quality improvement according to the target criterion of reclamation works efficiency. Practical implications. The obtained results are aimed at improving the methodological bases for management of the manmade lands reclamation process based on the choice of its mechanization means.

Мета. Теоретичне обґрунтування засад та розробка рекомендацій щодо вибору технологічного варіанту формування якості земель техногенного походження, які б відповідали вимогам раціонального використання коштів на рекультивацію та збереження придатності відтворених земель до використання за сільськогосподарським напрямом, як таким, що має найвищі вимоги щодо агрофізичних характеристик ґрунту. Методика. У процесі дослідження використано метод теоретичного узагальнення та систематизації (для визначення особливостей формування якісних характеристик техногенного ґрунту з використанням засобів механізації рекультиваційних робіт), аналітичний (для визначення факторів, що впливають на результативність відтворення земель в умовах відкритих гірничих розробок), порівняння (для аналізу ефективності різних варіантів механізації рекультиваційних робіт). Результати. Здійснено аналіз впливу технічних засобів механізації рекультиваційних робіт на якість земель, що підлягають відтворенню в умовах відкритих гірничих розробок. Запропоновано методичний підхід до вибору варіанту механізації робіт з рекультивації земель за показниками сформованої якості техногенних земель сільськогосподарського призначення, як чинника їх грошової оцінки, та рівнем витрат на їх відтворення. Розроблено рекомендації щодо управління якістю техногенних земель шляхом технічного забезпечення процесу формування їх споживчих властивостей, скерованого на досягнення сприятливого співвідношення, з одного боку, між якістю та, відповідно, грошовою оцінкою техногенних угідь, а з іншого – витратами на їх відтворення. Наукова новизна. Запропоновано науково-методичний підхід до вибору технічного устаткування для проведення рекультиваційних робіт, який відрізняється урахуванням двох чинників – витрат на рекультивацію та якість техногенних земель, і дозволяє визначити пріоритетність заощадження витрат або покращення якості земель за цільовим критерієм ефективності рекультиваційних робіт. Практична значимість. Отримані результати спрямовані на удосконалення методичних основ управління процесом відтворення техногенних земель на основі вибору засобів його механізації.

Цель. Теоретическое обоснование принципов и разработка рекомендаций относительно выбора технологического варианта формирования качества земель техногенного происхождения, соответствующего требованиям рационального использования средств на рекультивацию и обеспечения пригодности воспроизводимых земель к сельскохозяйственному использованию, предусматривающему наиболее высокие требования к агрофизическим характеристикам почв. Методика. В процессе исследования использованы метод теоретического обобщения и систематизации (для определения особенностей формирования качественных характеристик техногенного грунта с использованием средств механизации рекультивационных работ), аналитический (для определения факторов, влияющих на результативность воспроизводства земель в условиях открытых горных разработок), сравнения (для анализа эффективности различных вариантов механизации рекультивационных работ). Результаты. Выполнен анализ влияния технических средств механизации рекультивационных работ на качество земель, подлежащих восстановлению в условиях открытых горных разработок. Предложен методический подход к выбору варианта механизации работ по рекультивации земель в зависимости от его влияния на качество техногенных земель сельскохозяйственного назначения как фактора денежной оценки и уровня затрат на их восстановление. Разработаны рекомендации по управлению качеством техногенных земель путем технического обеспечения процесса формирования их потребительских свойств, направленного на достижение благоприятного соотношения, с одной стороны, между качеством и, соответственно, денежной оценкой техногенных угодий, а с другой – затратами на их восстановление. Научная новизна. Предложен научно-методический подход к выбору технического оборудования для проведения рекультивационных работ, позволяющий на основе учета затрат на рекультивацию и качества техногенных земель определять приоритетность экономии затрат или улучшения качества земель согласно целевому критерию эффективности рекультивационных работ. Практическая значимость. Полученные результаты направлены на совершенствование методических основ управления процессом восстановления техногенных земель на основе выбора средств его механизации.
Keywords: land quality; reclamation costs; monetary valuation of lands; reclamation technology; reclamation efficiency